Proprioception 3 years after shoulder arthroplasty in 3D motion analysis: a prospective study - Maier, Michael Wolfgang; Thielen, Mirjam; Dreher, Thomas; Wolf, Sebastian Immanuel; Zeifang, Felix; Loew, Markus (Archives of orthopaedic and trauma surgery, 2012)
BackgroundThis prospective study evaluated the development of proprioception over the course of 3 years after shoulder arthroplasty.MethodsTwenty-one patients were enrolled who underwent total shoulder arthroplasty (n = 10) or hemiarthroplasty (HEMI) (n = 11) for shoulder osteoarthritis. All patients were examined 1 day before the operation, 6 months and 3 years after surgery in a motion analysis study with an active angle-reproduction (AAR) test.ResultsOverall proprioception measured by the AAR deteriorated significantly 3 years after surgery [from 6.6° (SD 3.1) to 10.3° (SD 5.7); p = 0.017] and was significantly worse than in the control group [10.3° (SD 5.7) vs. 7.8° (SD 2.3); p = 0.030). In the HEMI subgroup, 3 years after shoulder replacement, there is a significant deterioration of proprioception at 30° of external rotation [from 3.1° (SD 3.5) to 12.8° (SD 10.7); p = 0.031]. On average, in the TSA subgroup proprioception deteriorated from 7.1° (SD 3.1) to 8.6° (SD 1.4) and in the HEMI subgroup from 6.1° (SD 2.1) to 12.4° (SD 8.3). The comparison of postoperative impairment of proprioception between the TSA and HEMI subgroup showed significantly worse proprioception for the HEMI subgroup at 30° of external rotation [9.8° (SD 10.1) vs. 1.6° (SD 6.3) in the TSA group; p = 0.046].ConclusionIn conclusion, proprioception that was measured by an AAR test remained unchanged or deteriorated 3 years after shoulder arthroplasty. The postoperative deterioration of proprioception was more distinctive in HEMI than in TSA group.